Sustainable infrastructure : principles into practice - Ainger, C. M.; Fenner, Richard (Delivering sustainable infrastructure., 2014)
'Sustainable Infrastructure' is a practical and accessible handbook which addresses the key principles of sustainability for engineers and built environment professionals. It outlines the critical changes needed to deliver more sustainable solutions and offers techniques to embed these changes as best practice in order to deliver high quality, economical and sustainable infrastructure across the globe.